Different Incidence of Venous Thrombosis in Patients with Inherited Deficiencies of Antithrombin III, Protein C and Protein S - Finazzi, G; Barbui, T (Thrombosis and Haemostasis, 1994)
A cohort study was undertaken to compare the incidence of thrombosis in patients with inherited deficiency of Antithrombin III (n = 9), Protein C (n = 36) and Protein S (n = 36). The patients were stratified for schedule of antithrombotic prophylaxis and followed for a total period of 160 patient-years. Seven venous thrombosis were observed for a total incidence of 4.3% pts.-ys. The incidence of thrombosis was not significantly different in patients of different age, sex and schedule of prophylaxis, although there was a trend to a lower incidence in young individuals and in those receiving long-term oral anticoagulation. Patients with AT III deficiency had an higher incidence of thrombosis than patients with Protein C or Protein S deficiency (12 vs. 2.8 vs. 3.3% pts.-ys., p <0.05), despite the fact that they were, on average, younger and more prophylaxed. This study suggests that congenital Antithrombin III deficiency constitutes a greater risk of thrombosis than congenital deficiences of Protein C and Protein S.